Critical evaluation of new Council of Europe guidelines concerning digital courts - Świerczyński, Marek Stanisław (Review of European and Comparative Law, 2022)
Digitalisation of courts plays an increasingly important role in dispute resolution. It has the ability to improve access to justice by facilitating faster and less costly access to courts, thereby making dispute resolution more effective and efficient. However, wide use of digital courts also has the potential to restrict access to justice. Attention needs to be given to issues of authentication and identification of the parties, digital divide, cybersecurity and personal data protection. This paper concerns recent guidelines of the Council of Europe that aim to fully address these issues and assist member States in ensuring that implemented digital techniques in the courts do not undermine human dignity, human rights and fundamental freedoms. The author answers and critically evaluates the specific questions and doubts relating to the content of the guidelines. The author’s recommendations can be taken into consideration by the Council of Europe in future updates of the guidelines.